2009
DOI: 10.1158/0008-5472.can-09-0755
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-11-Keto-β-Boswellic Acid Inhibits Prostate Tumor Growth by Suppressing Vascular Endothelial Growth Factor Receptor 2–Mediated Angiogenesis

Abstract: The role of angiogenesis in tumor growth and metastasis is well established. Identification of a small molecule that blocks tumor angiogenesis and is safe and affordable has been a challenge in drug development. In this study, we showed that acetyl-11-keto-B-boswellic acid (AKBA), an active component from an Ayurvedic medicinal plant (Boswellia serrata), could strongly inhibit tumor angiogenesis. AKBA suppressed tumor growth in the human prostate tumor xenograft mice treated daily (10 mg/kg AKBA) after solid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 198 publications
(151 citation statements)
references
References 37 publications
(41 reference statements)
6
144
0
1
Order By: Relevance
“…Our present investigation showed that both mRNA and protein expression of VEGF were dose-dependently suppressed by nitidine chloride via STAT3 inhibition in human gastric cancer cells. VEGF was initially thought to mediate its signaling in a paracrine manner by acting on neighboring endothelial cells via VEGFR2, which was specifically expressed on the endothelial cell surface and believed to regulate the majority of the angiogenic effects of VEGF (23,36,41). In this study, we found that nitidine chloride dose-dependently inhibited the phosphorylation of VEGFR2 (Tyr 1,175 ) in HUVECs, which may lead to the inhibition of a number of downstream signaling cascades.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Our present investigation showed that both mRNA and protein expression of VEGF were dose-dependently suppressed by nitidine chloride via STAT3 inhibition in human gastric cancer cells. VEGF was initially thought to mediate its signaling in a paracrine manner by acting on neighboring endothelial cells via VEGFR2, which was specifically expressed on the endothelial cell surface and believed to regulate the majority of the angiogenic effects of VEGF (23,36,41). In this study, we found that nitidine chloride dose-dependently inhibited the phosphorylation of VEGFR2 (Tyr 1,175 ) in HUVECs, which may lead to the inhibition of a number of downstream signaling cascades.…”
Section: Discussionmentioning
confidence: 62%
“…Formation of tubular structures of endothelial cell was studied in vitro as previously described (23). HUVECs were pretreated with nitidine chloride (5 and 10 mmol/L) for 1 hour and then seeded onto the Matrigel layer in 48-well plates at a density of 5 Â 10 4 to 1 Â 10 5 cells per well.…”
Section: Endothelial Cell Capillary-like Tube Formation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the oral administration of AKBA (50-200 mg/kg) dose-dependently inhibited the growth of colorectal tumors with no adverse side effects. Other studies showed that BA and its novel cyano derivative of 11-keto-b-boswellic acid inhibited Ehrlich ascites tumor [73,74], novel 11-keto-b-boswellic acid inhibited promyelocytic leukemia cells, HL-60, in both ascites and solid tumor model, was mediated through the inhibition of topoisomerase I and II [75] and AKBA suppressed human prostate tumor xenografts in nude mice [76]. Shah et al showed that 24-NH2 substituted b-boswellic acid derivatives exhibited much more potent apoptosis induction and cell proliferation inhibition than their parent 24-COOH compounds.…”
Section: Boswellic Acidmentioning
confidence: 98%